An Audit of Rational Use of Antibiotics in a Tertiary Hospital (Delta Medical College Journal, 2014)
Background: Drug can cure ailment when used rationally on the other hand they may become harmful or even may threaten a life when used irrationally. Absence of guidelines for antibiotic use, protocols for rational therapeutics and infection control committees, have led to overuse and misuse of antimicrobials even in different specialized units in hospitals. Objective: The study has been designed to get a picture of use of antibiotics in a tertiary care hospital of Bangladesh. Materials and method: Cross sectional study was conducted in the department of Medicine of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh, for 3 months from 1st January 2009 to 31st March 2009. Admitted patients of Medicine unit-1 who got antibiotics were included in the study. Total number of patients was 1563. Results: Five hundred out of 1563 patients were prescribed antibiotics (38%). Out of 500 prescriptions, 68(14%) prescriptions were found irrational. Conclusion: Continuous surveillance should be carried out to reduce the irrational use of antibiotics. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20526 Delta Med Col J. Jul 2014; 2(2): 64-67